Development of 2013 Curriculum Integrated Thematic Teaching Materials With A Scientific Approach in Class 1 Elementary School - Fitria Kumala Sari; Rakimahwati Rakimahwati; Yanti Fitria (Postgraduate School, Universitas Negeri Padang, 2019)
This research is a development research on teaching materials in the first grade of elementary school. This research uses Research and Development (R & D) research with the ADDIE Model. This teaching material was developed using the ADDIE development model where this activity begins with analysis (analysis), design (design), development (develop), implementation (implement) and evaluation (evaluate). The disseminate stage is only carried out on a limited scale, namely at SDN 25 Jati Tanah Tinggi, Padang City. The results of the RPP validity are declared valid with an average of 3.60. The results of the average teaching material obtained were 3.50 from expert validate and 3.70 from practical validate with very valid categories. The practical test results from the implementation of the RPP with a percentage of 3.80 with a very practical category. Assessment of teacher responses was 3.80 and assessment of students' responses to 3.80 in a very practical category. Assessment of student activities obtained 81.36 active categories. Learning outcomes assessment shows that the percentage of completeness results above the KKM. Based on these results, it can be concluded that thematic teaching materials with a Scientific approach for elementary school class I students are valid, practical, and effective Key Word : Integrated Teaching, Scientific, Thematic Materia